2018
DOI: 10.21577/0100-4042.20170281
|View full text |Cite
|
Sign up to set email alerts
|

HIDRÓLISE ENZIMÁTICA, FERMENTAÇÃO E PRODUÇÃO DE BIOCOMBUSTÍVEIS ATRAVÉS DA COROA DE Ananas comosus

Abstract: Problems related to the use of fossil fuels and greenhouse gas emissions have become global concerns. To address this issue, the strategy adopted in the present study was to use Ananas comosus residues as a source of fermentable carbohydrates to produce second generation ethanol and briquettes. The demand for biofuel is addressed in the present study by the integrated processing of several stages of treatment of the lignocellulosic substrate: chemical characterization, pretreatment, enzymatic hydrolysis and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
1
0
2
Order By: Relevance
“…The pH values ranging from 5.0 to 6.5 resulted in invertase production varying from 13.0 to 14.0 U/mL. Similar behaviour was observed of A. niger IBK1, when invertase production was higher in acidic pH range (4.0-6.0), with maximum invertase production occurring at pH=5.0 ( 16 ). Dinarvand et al .…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The pH values ranging from 5.0 to 6.5 resulted in invertase production varying from 13.0 to 14.0 U/mL. Similar behaviour was observed of A. niger IBK1, when invertase production was higher in acidic pH range (4.0-6.0), with maximum invertase production occurring at pH=5.0 ( 16 ). Dinarvand et al .…”
Section: Resultssupporting
confidence: 57%
“…Silva et al . ( 16 ) showed that pineapple crown is a potential carbon source, containing xylose and mostly glucose as constituents, and hence is an attractive residue for microbial growth. The predicted versus observed values revealed a good correlation between the model and experimental invertase production.…”
Section: Resultsmentioning
confidence: 99%
“…Os resultados estão apresentados na Tabela 1. A Figura 1 mostra que com 6h ocorre um decaimento na concentração de glicose e com 14h na concentração de xilose, demonstrando que a produção de etanol está associada ao consumo dos açúcares pela levedura (SILVA et al, 2018). A fermentação é o processo anterior à destilação e é a partir desta etapa que ocorre a degradação da glicose e outros nutrientes orgânicos em vários produtos, para geração de energia sob a forma de adenosina trifosfato, ou ATP (LEHNINGER et al, 2006).…”
Section: Resultados E Discussõesunclassified
“…Ademais, essas condições para geração de combustível líquido fazem da matériaprima e do produto, fontes sustentáveis. [15][16][17] As indústrias de biocombustíveis têm empenhado grande esforço para estabelecer o melhor pré-tratamento da biomassa lignocelulósica para produção de etanol 2G. Exemplos de resíduos de biomassa utilizados para produção desse biocombustível são o bagaço e a palha da canade-açúcar, estudados por meio de diferentes prétratamentos para aumentar a oferta de celulose na obtenção do etanol 2G por meio dos seus açúcares fermentescíveis.…”
Section: Introductionunclassified